2010
DOI: 10.1111/j.1464-410x.2010.09591.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative peripheral frozen sections do not significantly affect prognosis after nerve‐sparing radical prostatectomy for prostate cancer

Abstract: RESULTS• Of all 188 prostatectomy specimens, 49 (26.1%) had positive surgical margins (PSM); these were found posterolaterally in 15 (30.6%), apically in 13 (26.5%), basally in 10 (20.4%) and at multiple sites in 11 (22.4%) specimens.• Intraoperative peripheral FS were positive in 19 (10.7%) patients, including 6.2% at urethral stump, 3.3% at lateral pedicles and 1.1% at bladder neck.• In organ-confined disease, BCR-free survival was 93.3% (111/119) for patients with negative surgical margins (NSM) and 72% (18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
0
29
1
Order By: Relevance
“…Most of the included studies were retrospective (74%) and only five studies (26%) were prospective in nature. Furthermore, the studies were performed mainly in Germany (seven studies) , the UK (four studies) , USA (three studies) , Turkey (two studies) , Italy , Romania , and Norway (one study each). The sample size (considering only the patients undergoing intraoperative FS) in the included studies ranged from 40 to 5392 patients.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the included studies were retrospective (74%) and only five studies (26%) were prospective in nature. Furthermore, the studies were performed mainly in Germany (seven studies) , the UK (four studies) , USA (three studies) , Turkey (two studies) , Italy , Romania , and Norway (one study each). The sample size (considering only the patients undergoing intraoperative FS) in the included studies ranged from 40 to 5392 patients.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…A total of 19 articles reporting on NS‐zone sampling techniques and NVB secondary resection were published between 2010 and 2019 . Table summarises all the studies reporting FS sampling and secondary resection of a PSM at the NVB.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Limited long-term follow-up exclusively in the contemporary prostate-specific antigen (PSA) era is also restricted to laparoscopy or open approaches. Only five cohorts [7][8][9][10][11] have published 10-yr biochemical recurrence (BCR), three for open prostatectomy [7][8][9] that report BCRFS rates ranging between 39% and 93%, depending on factors such as stage, Gleason score, or surgical margins, and two for laparoscopy [10,11] that document overall BCRFS rates of 76% and 71%, respectively.…”
mentioning
confidence: 99%
“…In contrast, another study that focused on intraoperative frozen sections as a way to spare NVB demonstrated a high rate of false negatives, potentially resulting in unjustified NVB resection, time consumption, and no significant effect on prognosis. [28,29] We did not obtain routine intraoperative frozen sections from our high-risk patients, but for a few patients we performed surgical margin biopsy, which was negative for all patients. This technique is appropriate only for certain high-risk patients.…”
Section: Discussionmentioning
confidence: 99%